Evaluasi Kualitas Layanan Kampus Inklusif: Pengaruh Dimensi Servqual terhadap Kepuasan Mahasiswa Penyandang Disabilitas - Ayuni Syazana; Xenia Cerry Novia; Muhammad Naufal Husain; Kamila Nurul Hanifah; Gheahaq Danty El Zahra (Public Service and Governance Journal, 2025)
An inclusive university education is the right of every individual, including students with disabilities. However, in Indonesia, this group still often faces various obstacles in accessing adequate campus facilities. The purpose of this study examines the extent to which campus service quality, according to the 5 dimensions of SERVQUAL, affects the satisfaction of active students with disabilities at Universitas Airlangga. Quantitative approach with survey data collection method with questionnaires to students with disabilities as the primary data source. Data were analyzed by multiple linear regression to test the effect of each service dimension on the level of respondent satisfaction. Test simultaneously (F test), see the influence of the five dimensions simultaneously, and also partially (t test) for each dimension. Based on the results of data analysis, all SERVQUAL dimensions are proven to simultaneously have a significant influence on the level of satisfaction of students with disabilities at Universitas Airlangga. Partially, each dimension does not show a significant effect, but the direction of the relationship found is positive. This finding emphasizes the importance of improving disability-friendly campus facilities and services in order to create a more inclusive learning environment.